The Lighting Environment, Its Metrology, and Non-visual Responses - Schlangen, Luc J. M.; Price, Luke L. A. (Frontiers in Neurology, 2021)
International standard CIE S 026:2018 provides lighting professionals and field researchers in chronobiology with a method to characterize light exposures with respect to non-visual photoreception and responses. This standard defines five spectral sensitivity functions that describe optical radiation for its ability to stimulate each of the five α-opic retinal photoreceptor classes that contribute to the non-visual effects of light in humans via intrinsically-photosensitive retinal ganglion cells (ipRGCs). The CIE also recently published an open-access α-opic toolbox that calculates all the quantities and ratios of the α-opic metrology in the photometric, radiometric and photon systems, based on either a measured (user-defined) spectrum or selected illuminants (A, D65, E, FL11, LED-B3) built into the toolbox. For a wide variety of ecologically-valid conditions, the melanopsin-based photoreception of ipRGCs has been shown to account for the spectral sensitivity of non-visual responses, from shifting the timing of nocturnal sleep and melatonin secretion to regulating steady-state pupil diameter. Recent findings continue to confirm that the photopigment melanopsin also plays a role in visual responses, and that melanopsin-based photoreception may have a significant influence on brightness perception and aspects of spatial vision. Although knowledge concerning the extent to which rods and cones interact with ipRGCs in driving non-visual effects is still growing, a CIE position statement recently used melanopic equivalent daylight (D65) illuminance in preliminary guidance on applying “proper light at the proper time” to manipulate non-visual responses. Further guidance on this approach is awaited from the participants of the 2nd International Workshop on Circadian and Neurophysiological Photometry (in Manchester, August 2019). The new α-opic metrology of CIE S 026 enables traceable measurements and a formal, quantitative specification of personal light exposures, photic interventions and lighting designs. Here, we apply this metrology to everyday light sources including a natural daylight time series, a range of LED lighting products and, using the toobox, to a smartphone display screen. This collection of examples suggests ways in which variations in the melanopic content of light over the day can be adopted in strategies that use light to support human health and well-being.